2011
DOI: 10.1089/gtmb.2011.0033
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of ThreeCYP2D6Nonfunctional Alleles (CYP2D6*3,*4, and*6) Within an Iranian Population (Mazandaran)

Abstract: Although the frequencies of CYP2D6 nonfunctional alleles have been extensively studied in most populations worldwide, limited information is available for those of the Iranian population. The present study aimed to determine the frequency of three CYP2D6 nonfunctional alleles (CYP2D6*3, *4, and *6) in the Mazandarani ethnic group among the Iranian population. A total of 100 unrelated healthy subjects living in Mazandaran, a Caspian province in the north of Iran, were selected. Lymphocytic genomic DNA was genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…A limitation of our study is the number of patients included. Previous studies have shown a low frequency of CYP2D6 PM subjects in the Iranian population (Kouhi et al, 2009; Hashemi-Soteh et al, 2011; Bagheri et al, 2015). In line with these findings, the number of PM patients was not high enough to analyze those patients separately.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A limitation of our study is the number of patients included. Previous studies have shown a low frequency of CYP2D6 PM subjects in the Iranian population (Kouhi et al, 2009; Hashemi-Soteh et al, 2011; Bagheri et al, 2015). In line with these findings, the number of PM patients was not high enough to analyze those patients separately.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the Iranian population and the ethnic background few studies indicate the most relevant CYP2D6 alleles (Kouhi et al, 2009; Hashemi-Soteh et al, 2011; Bagheri et al, 2015). Accordingly, we decided to genotype the breast cancer patients of our study for the CYP2D6 alleles ∗ 1, ∗ 2, ∗ 4, ∗ 5, ∗ 6, ∗ 10, ∗ 17 , and ∗ 41 as well as the gene duplication to comprehensively cover CYP2D6 alleles representative of the Iran population (Isfahan province).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 5 mL of peripheral blood was collected in EDTA from each person, and genomic DNA was extracted according to established protocols . The GAP‐PCR protocol, described by Baysal and Huisman, was primarily applied for all samples to detect α3.7 (3.7 kb), α4.2 (4.2 kb), ‐‐MED, ‐‐20.5, and ‐‐SEA variations, as a primary screening test .…”
Section: Methodsmentioning
confidence: 99%
“…The samples were then subjected to a final extension step at 72 °C for 5 min. A 6-μl aliquot of each PCR product was run on a 1% flatbed agarose gel to check for positive amplification [ 6 , 18 ].…”
Section: Methodsmentioning
confidence: 99%